Osteoprotegerin Prevents Intracranial Aneurysm Progression by Promoting Collagen Biosynthesis and Vascular Smooth Muscle Cell Proliferation - Takeshi Miyata; Manabu Minami; Hiroharu Kataoka; Kosuke Hayashi; Taichi Ikedo; Tao Yang; Yu Yamamoto; Masayuki Yokode; Susumu Miyamoto (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Decreased extracellular matrix formation and few vascular smooth muscle cells (VSMCs) in cerebral vascular walls are the main characteristics of intracranial aneurysm (IA) pathogenesis. Recently, osteoprotegerin was reported to activate collagen biosynthesis and VSMC proliferation via the TGF‐β1 (transforming growth factor‐β1) signaling. This study aimed to investigate whether osteoprotegerin can prevent IA progression in rats through enhanced collagen expression and VSMC proliferation. Methods and Results IAs were surgically induced in 7‐week‐old male Sprague–Dawley rats; at 1‐week post‐operation, recombinant mouse osteoprotegerin or vehicle control was continuously infused for 4 weeks into the lateral ventricle using an osmotic pump. In the osteoprotegerin‐treatment group, the aneurysmal size was significantly smaller (37.5 μm versus 60.0 μm; P<0.01) and the media of IA walls was thicker (57.1% versus 36.0%; P<0.01) than in the vehicle‐control group. Type‐I and type‐III collagen, TGF‐β1, phosphorylated Smad2/3, and proliferating cell nuclear antigen were significantly upregulated in the IA walls of the osteoprotegerin group than that in the control group. No significant difference was found in the expression of proinflammatory genes between the groups. In mouse VSMC cultures, osteoprotegerin treatment upregulated the expression of collagen and TGF‐β1 genes, and activated VSMC proliferation; the inhibition of TGF‐β1 signaling nullified this effect. Conclusions Osteoprotegerin suppressed the IA progression by a unique mechanism whereby collagen biosynthesis and VSMC proliferation were activated via TGF‐β1 without altering proinflammatory gene expression. Osteoprotegerin may represent a novel therapeutic target for IAs.